Supraumbilical gastroschisis - E.G. Dunne; C. Li; E. Kessler (Elsevier, 2022)
Gastroschisis is a rare congenital defect of the ventral abdominal wall through which abdominal contents herniate outside of the body without a peritoneal sac. The most common location of the defect is to the right of the umbilicus, however, there have been case reports of defects in alternate locations along the abdominal wall, particularly on the left side. Here we describe a case of a baby born with a gastroschisis-like defect in the midline supraumbilical abdominal wall, the only such case described in the literature, to our knowledge. The defect was small with herniated bowel and loss of domain in the abdomen requiring delayed closure with a silo. Cases of gastroschisis in unusual locations bring into question the pathogenesis of such defects, a topic which remains controversial.